Elevation of alpha-1 acid glycoprotein during acute infection increases clozapine levels without signs of intoxication - Spangemacher, Moritz; Hart, Xenia Marlene; Saalfrank, Elea; Gründer, Gerhard; Reinwald, Jonathan Rochus; Sartorius, Alexander (Journal of clinical psychopharmacology, 2024)
An abstract is unavailable.
Gesehen am 24.02.2025